The Impact Of Public Space On The Improvement Of The MSME Economy In The Dumai Islamic Center - Sadam Handika; Agus Susilo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
It functions as a center for religious activities, but also as a driving force in local economic empowerment, especially for Micro, Small, and Medium Enterprises (MSMEs). Through a management strategy based on community needs and the concept of Islamic Corporate Social Responsibility (ICSR), DIC is able to create a business ecosystem that supports the growth of MSMEs in Dumai City. The existence of DIC has a positive impact in the form of increasing the income of MSME actors, the availability of business support facilities, and the creation of a conducive trading environment. Although still facing several obstacles such as limited infrastructure during the rainy season, the manager's efforts in providing basic facilities have made a significant contribution to increasing the competitiveness and resilience of MSMEs. In addition to supporting the welfare of MSME actors, DIC also strengthens the local economic turnover and becomes a model for integration between social, economic, and religious functions that support sustainable development in Dumai City.